Decrease in newly generated oligodendrocytes leads to motor dysfunctions and changed myelin structures that can be rescued by transplanted cells. Issue 12 (12th September 2016) - Schneider, Sarah; Gruart, Agnès; Grade, Sofia; Zhang, Yina; Kröger, Stephan; Kirchhoff, Frank; Eichele, Gregor; Delgado García, José M.; Dimou, Leda
Abstract : NG2‐glia in the adult brain are known to proliferate and differentiate into mature and myelinating oligodendrocytes throughout lifetime. However, the role of these newly generated oligodendrocytes in the adult brain still remains little understood. Here we took advantage of the Sox10‐iCreER T2 x CAG‐eGFP x Esco2 fl/fl mouse line in which we can specifically ablate proliferating NG2‐glia in adult animals. Surprisingly, we observed that the generation of new oligodendrocytes in the adult brain was severely affected, although the number of NG2‐glia remained stable due to the enhanced proliferation of non‐recombined cells. This lack of oligodendrogenesis led to the elongation of the nodes of Ranvier as well as the associated paranodes, which could be locally rescued by myelinating oligodendrocytes differentiated from transplanted NG2‐glia deriving from wildtype mice. Repetitive measurements of conduction velocity in the corpus callosum of awake animals revealed a progressive deceleration specifically in the mice lacking adult oligodendrogenesis that resulted in progressive motor deficits. In summary, here we demonstrated for the first time that axon function is not only controlled by the reliable organization of myelin, but also requires a dynamic and continuous generation of new oligodendrocytes in the adult brain. GLIA 2016;64:2201–2218 Main Points: Ablation of proliferating NG2‐glia leads to reduced oligodendrogenesis in the adult brain. This leads to nodal changes that can be rescued by transplanted cells, as well as to decrease in conduction velocity and to consequent movement deficits.